Pengaruh Latihan Bulutangkis Dala Meningkatkan Kapasitas Paru Paru Pada Masyarakat Pattalassang Kabupaten Gowa - Alimin Hamzah; Muslim Bin Ilyas; Asri Awal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
Muslim Bin Ilyas 2024. The Effect of Badminton Training in Increasing Lung Capacity in the Patalasang Community, Gowa Regency. The formulation of the problem in this research is the Effect of Badminton Training in Increasing Lung Capacity in the Patalasang Community, Gowa Regency. Meanwhile, the aim of this research is to find out whether there is an effect of badminton training in increasing lung capacity in the Patalasang community, Gowa Regency. The type of research that will be used in this research is quantitative descriptive analysis. In this research design, research subjects are selected using purposive sampling based on certain characteristics, research so that the research subjects are homogeneous. Meanwhile, data analysis uses SPSS 21 using descriptive tests, normality tests and hypothesis tests.Based on the results of the analysis, the results of the data processing tests show that there is an influence of badminton training in increasing lung capacity in the Patalasang community, Gowa Regency. that the initial score obtained by the Patalasang Community of Gowa Regency before being given badminton training was 422.00 and the final score obtained by the Patalasang Community of Gowa Regency after being given badminton training was 451.50, so this identifies that the impact of the Effectiveness of Badminton Training in Increasing Lung Capacity in the Patalasang Community of Gowa Regency is equal to 29,500. involving 20 samples.